1953
DOI: 10.1037/h0060458
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of duration of therapy from the Rorschach Test.

Abstract: mained in t.reatment complained more often of obsessions, phobias, depression, poor concentration and anxiety. Patients who terminated prematurely complained more often of purely organic symptoms, getting in trouble, and paranoid and schizoid feelings. It is suggested that more attention be paid to motivating the patient to go into treatment before such treatment is offered and that alternative methods be used to deal with types of patients who probably could not be induced to accept the traditional forms of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1958
1958
1974
1974

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 2 publications
2
30
0
Order By: Relevance
“…They are more pessimistic about the future, show some resentment and negative attitudes toward hospitalization, have greater difficulty in making friends in the hospital, and are apparently more disturbed by family and social problems outside of the hospital. These findings based on patients' self-report, are supported by behavioral ratings of nurses and aides; these ratings also suggest poorer adjustment by irregular discharge patients in the hospital.2 6 Attempts to use standardized psychological tests to predict irregular discharge have not been notably successful. In three studies, 29 -31 a single instrument, the Minnesota Multiphasic Personality Inventory (MMPI) 110 • pt 1 was used.…”
Section: Studies Of Sick-role Behaviormentioning
confidence: 82%
See 1 more Smart Citation
“…They are more pessimistic about the future, show some resentment and negative attitudes toward hospitalization, have greater difficulty in making friends in the hospital, and are apparently more disturbed by family and social problems outside of the hospital. These findings based on patients' self-report, are supported by behavioral ratings of nurses and aides; these ratings also suggest poorer adjustment by irregular discharge patients in the hospital.2 6 Attempts to use standardized psychological tests to predict irregular discharge have not been notably successful. In three studies, 29 -31 a single instrument, the Minnesota Multiphasic Personality Inventory (MMPI) 110 • pt 1 was used.…”
Section: Studies Of Sick-role Behaviormentioning
confidence: 82%
“…1 · 5 • 6 These responses are less stereotyped 6 and reflect both intelligence and the patient's motivation to cooperate. Other indices derived from the Rorschach test do not seem to yield replicable results.…”
Section: Studies Of Sick-role Behaviormentioning
confidence: 96%
“…Of the variables investigated, socioeconomic class has been demonstrated as a poten~predictor, accounting for the majority of dropouts (Auld & Myers, 1954;Frank, Gliedman, Imber, Nash, & Stone, 1957;Gallagher & Kanter, 1961;Garfield & Affleck, 1959;Gibby, 1953Gibby, , 1954Gleidman, 1957;Hiler, 1954Hiler, , 1958Hiler, , 1959Imber, Nash, & Stone, 1956;Lorr, Katz, & Rubinstein, 1958;Rosenthal & Frank, 1958;Rubinstein & Lorr, 1956;Sullivan, Miller, & Smelser, 1958;Winder & Hersko, 1955). Utilizing a broad band of demographic variables, this study investigated the characteristics of adult and child dropouts at a community mental health outpatient clinic.…”
mentioning
confidence: 96%
“…The Long-Term therapy group was found to have given more adequate responses to Card IV (responses with neutral tone and good form). Application of the Gibby et al (1953) approach to this college student population revealed two significant differences. The Change group was higher than the No Change group (p < .05) on both Sum C and m. In addition, there were several marked trends which did not reach significance.…”
Section: Results From Related Literaturementioning
confidence: 98%
“…Analysis of the data took three forms. The first was an application of approaches revealed by the related literature to have promise (Auld & Eron, 1959;Dana, 1954;Gibby, Stotsky, Hiler, & Miller, 1954;Gibby, Stotsky, Miller, & Hiler, 1953;Koltov & Meadow, 1953). The second was the application of the Klopfer et al (1951) Rorschach Prognostic Rating Scale (RPRS) to the Rorschach protocols in the sample.…”
Section: Discussionmentioning
confidence: 99%